Community health workers and breast cancer early detection in low- or middle-income countries: a systematic scoping review of the literature - O'Donovan, J; Newcomb, A; MacRae, M; Vieira, D; Olinyofor, C; Ginsburg, O (BMJ Publishing Group, 2020)
Background Breast cancer is the leading cause of female mortality in low- and middle-income countries (LMICs). Early detection of breast cancer, either through screening or early diagnosis initiatives, led by Community Health Workers (CHWs) has been proposed as a potential way to address the unjustly high mortality rates. We therefore document: (i) Where and how CHWs are currently deployed in this role; (ii) How CHWs are trained, including the content, duration, and outcomes of training; and (iii) The evidence on costs associated with deploying CHWs in breast cancer early detection.